2022
DOI: 10.1002/aelm.202200601
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Ferroelectric Phase Stabilization via the Clamping Effect in Ferroelectric Hafnium Zirconium Oxide Thin Films

Abstract: The presence of the top electrode on hafnium oxide‐based thin films during processing has been shown to drive an increase in the amount of metastable ferroelectric orthorhombic phase and polarization performance. This “Clamping Effect,” also referred to as the Capping or Confinement Effect, is attributed to the mechanical stress and confinement from the top electrode layer. However, other contributions to orthorhombic phase stabilization have been experimentally reported, which may also be affected by the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 75 publications
0
36
0
Order By: Relevance
“…It is reported that the stress of the HZO thin films is related to the coefficients of thermal expansion mismatch with the employed electrodes. , The Figure c summarizes the 2Pr (with 4 MV/cm electric field) of different electrode devices and the corresponding thermal expansion coefficient. It can be seen that the thermal expansion coefficient is 4.5 × 10 –6 /°C, 5.2 × 10 –6 /°C, and 8.5 × 10 –6 /°C for W/Mo/ITO electrodes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the stress of the HZO thin films is related to the coefficients of thermal expansion mismatch with the employed electrodes. , The Figure c summarizes the 2Pr (with 4 MV/cm electric field) of different electrode devices and the corresponding thermal expansion coefficient. It can be seen that the thermal expansion coefficient is 4.5 × 10 –6 /°C, 5.2 × 10 –6 /°C, and 8.5 × 10 –6 /°C for W/Mo/ITO electrodes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The relative volume fraction of t + o phases (f t+o ) can be calculated through comparison between the integrated intensity of the Pearson VII shape fit to the t + o peak and the integrated intensities of shapes fit to all t + o and monoclinic peaks, as conducted in prior work. [46] These fractions were determined to be 0.97 ± 0.05, 0.94 ± 0.09, and 0.95 ± 0.04, for the films processed with TaN, Pt, and W, respectively. The PMA sample processed with an Hf top electrode has comparatively little orthorhombic phase, as evidenced by the large total intensity from the (111) and (111) monoclinic (m 1 and m 2 , respectively) diffraction peaks and low f t+o of 0.33 ± 0.05.…”
Section: Effects Of Top Electrode On Pma Hzo Phase and Polarizationmentioning
confidence: 93%
“…Pt [64] 5.65 0.90 with observations in previous work. [46] Specifically, the decrease in diffraction angle is resultant from a reduction in the biaxial tensile stress state of the HZO and the transformation of 5% of the volume of the film from the t + o phases to the monoclinic phase. This phase transformation occurs because the removal of the top electrode allows for local volumetric expansion and formation of the high molar volume monoclinic phase.…”
Section: Effect Of Replacement Processing On Hf 05 Zr 05 O 2 Phasementioning
confidence: 99%
See 1 more Smart Citation
“…[10,11,12] One of the most promising strategies used to stabilize the orthorhombic (o-) phase and enhance the ferroelectric properties of HZO films was the use of tensile stress. [13,14,15] Different tensile stress levels can be obtained by the appropriate choice of the electrodes, since the difference in the thermal expansion coefficient (TEC) of HZO and the electrode is one of the important origins of tensile stress when the films are cooled down to room temperature.…”
Section: Introductionmentioning
confidence: 99%